Metal-ion-binding properties of ulvan extracted from Ulva clathrata and structural characterization of its complexes. (15th November 2021) - Chi, Yongzhou; Li, Huining; Fan, Li; Du, Chunying; Zhang, Jingliang; Guan, Huashi; Wang, Peng; Li, Rong
Abstract: The acidic polysaccharide ulvan extracted from the cell wall of the green algae Ulva is a good ligand for metal ions. Therefore, the adsorption properties of the U. clathrata derived ulvan toward Ca(II), Zn(II), Co(II), Cu(II), and Cr(III) were investigated in this study. The results demonstrate that ulvan exhibited good metal ion adsorption capacity at pH 7 and 50 °C. These adsorption processes can largely be explained by the Freundlich isotherm model and the pseudo-second-order kinetic model. The order of the adsorption capacity and affinity is as follows: Cr(III) > Cu(II) > Zn(II) ≈ Co(II) > Ca(II) and Cr(III) > Zn(II) > Co(II) ≈ Cu(II) > Ca(II). Furthermore, structural characterization revealed that the hydroxyl and carboxyl groups were the main functional groups involved in metal ion binding. Unlike the divalent metal ions, Cr(III) can trigger crosslinking of the ulvan chains, and its adsorption capacity was approximately 4.0 mmol/g. Highlights: Metal adsorption processes of ulvan were well described by Freundlich isotherm model. The order of adsorption affinity was Cr(III) > Zn(II) > Co(II) ≈ Cu(II) > Ca(II). Hydroxyl and carboxyl groups on the ulvan chains involved in metal ion binding. Cr(III) can trigger cross-linking of the ulvan chains.